Growth, weight gain and BMI in virally suppressed children on antiretroviral therapy with specific reference to dolutegravir - Erik Belfrage; Sandra Soeria-Atmadja; Lars Navér (BMC, 2023)
Abstract Background Pediatric HIV infection cause retardation in height and weight. However, effective antiretroviral therapy (ART) result in desirable weight gain. Concerns have emerged regarding excessive weight gain related to the integrase inhibitor dolutegravir in adults but knowledge about the circumstances in children/adolescents is limited. We studied if dolutegravir containing ART or switch to dolutegravir affected body mass index (BMI) and described height development in the Stockholm pediatric/adolescent HIV cohort. Methods A retrospective cohort study of height, weight and BMI in relation to ART in 94 children/adolescents living with HIV. Results At last documented visit 60/94 children/adolescents were on dolutegravir, 50 had switched from a protease inhibitor or non-nucleoside reverse transcriptase inhibitor. Height standard deviation score (SDS) increased between first and last visit from mean height SDS -0.88 (16 had SDS < -2 and 6 SDS < -3) to -0.32 (four had SDS < -2). Mean BMI SDS increased from -0.15 to 0.62 in girls, but not (-0.20 to 0.09) in boys. The number of girls ≥ 12 years with BMI SDS ≥ 2 increased significantly from 0/38 to 8/38 and totally 9/50 (18%) girls and 4/44 (9%) boys had BMI SDS ≥ 2 at last visit. There was no difference in height or weight gain between different ART regimens. BMI SDS remained stable in 22/50 children switching to dolutegravir, decreased in 13 and increased in 15. Conclusion Adolescent girls gained weight to a greater extent than expected but independently of ART. We found no association between dolutegravir alone or combined with tenofovir alafenamide fumarate (TAF) and excessive weight gain. Height development was within normal range.